PEDAGOGICAL CONDITIONS FOR THE FORMATION OF MANAGERIAL COMPETENCIES OF FUTURE TEACHERS THROUGH PRACTICE-ORIENTED EDUCATIONAL TASKS - Kurkina, Nadirya; Starodubtseva, Lyubov; VictorovnaSuldina, Olga; Semenova, Olga (Revista Inclusiones, 2020)
The relevance of the issues of the formation of future teachers’ managerial competencies is due to the increased requirements for the quality of training and complication of the conditions for organizing the educational process, which determines the strengthening of requirements for professional competence and the need to prepare for a new role – a teacher-manager. When analyzing the problem, a complex of theoretical and empirical methods is used: a systematic analysis of scientific and methodological works, generalization of pedagogical experience, observation and analysis of the results of pedagogical activity, allowing the authors to consider this problem taking into account many factors that affect the process of forming the managerial competencies of future teachers.